Manhaj asy-Syaikh Nawawi al-Bantāni fi ‘Ardh al-Qirā’āt - Hana Natasya (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This research discusses the Qirā’āt in Tafsīr al-Munīr li Mā'alim at-Tanzīl al-Mufassar 'an Wujūh Mahāsin at-Ta'wīl known as Tafsīr Marāh Labīd Li Kasyf Ma’na Al-Qur’ān al-Majīd by Shaykh Nawawi al-Bantāni. He has been highly recognized as a commentator (Mufassir). His works are still being refered extensively in Indonesia to this day. His tafsir contains a lot of discussion about qirā’āt. The tafseer contained various kinds of qirā’āt. Among them are qirā’āt mutawātirah, qirā’āt āhad, qirā’āt syādzdzah, qirā’āt narrated by companions and tabi'in, and sometimes Syaikh Nawawi incorporates various narrations in one verse. The author also attributes every qirā’āt to it's reader and it's narrations, and also to the inhabitants of a country, and the Public acknowledgment or 'al-bāqīn' (other readers those mentioned), or to' āmmah '. Sometimes it also does not attribute to anyone. Syaikh Nawawi also mentions qirā’āt which stated in manuscripts and private manuscripts of the Ǻahaby. He also mentions the 'waqaf' dan 'ibtida' in the interpretation in that verse. Sometimes he states 'qirā'āt mutawātirah' and ‘qirā’āt syādzdzah’ but only in a few places. Also he do 'tarjih' on some qira'at. Shaykh Nawawi also gives 'taujih' to qirā'āt mutawātirah and syādzdzah and reveals it's 'illat' as well as reasons for it in terms of language, nahwu's and other disciplines and implications resulting from the taujih to the field of theology and islamic jurisprudence.